THE JURIDIZATION OF TECHNICAL NORMS - Довженко, Євгенія Володимирівна; Чечет, Анна Михайлівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: to formulate a theoretical and legal characteristic of the juridization of technical norms on the basis of a study of general theoretical approaches to the definition of the concept and essence of the juridization. Methods: analysis and synthesis, formal-logical, cognitive-analytical, etc. Results: generalized existing scientific developments on the concept and components of the legalization, identified goals, objects and subjects of the juridization of technical norms, identified the prerequisites for further increasing the value of the legalization of technical norms in legal regulation of public relations. Discussion: the article contains a general theoretical study of the concept of the juridization of technical norms. The author presents an analysis of existing theoretical and legal approaches to the definition of the juridization. The importance of technological progress and its achievements in the life of modern society allows the author to formulate a list of prerequisites for the juridization of technical norms, as well as to justify the need for its implementation. The concept of the juridization is defined as the implementation by the state of a legal assessment of certain norms from the standpoint of their suitability as regulators of public relations. The goals of the juridization are to provide technical rules with the means to further streamline the impact on society; transformation of non-legal methods into legal ones with the inclusion of the latter into a new cognitive-semantic context of the subject and method of legal science; in providing certain phenomena with the properties of legal facts; in the creation of new legal institutions. The object of the juridization can be norms of behavior that are fixed by law, but do not have legal characteristics, as well as social and professional norms. The state is the mains subject of the juridization.